Do all roads lead to Rome? The role of neuro-immune interactions before birth in the programming of offspring obesity - Jasoni, Christine L.; Sanders, Tessa R.; Kim, Dong Won (Frontiers in Neuroscience, 2015)
The functions of the nervous system can be powerfully modulated by the immune system. Although traditionally considered to be quite separate, neuro-immune interactions are increasingly recognized as critical for both normal and pathological nervous system function in the adult. However, a growing body of information supports a critical role for neuro-immune interactions before birth, particularly in the prenatal programming of later-life neurobehavioral disease risk. This review will focus on maternal obesity, as it represents an environment of pathological immune system function during pregnancy that elevates offspring neurobehavioral disease risk. We will first delineate the normal role of the immune system during pregnancy, including the role of the placenta as both a barrier and relayer of inflammatory information between the maternal and fetal environments. This will be followed by the current exciting findings of how immuno-modulatory molecules may elevate offspring risk of neurobehavioral disease by altering brain development and, consequently, later life function. Finally, by drawing parallels with pregnancy complications other than obesity, we will suggest that aberrant immune activation, irrespective of its origin, may lead to neuro-immune interactions that otherwise would not exist in the developing brain. These interactions could conceivably derail normal brain development and/or later life function, and thereby elevate risk for obesity and other neurobehavioral disorders later in the offspring’s life.